2007
DOI: 10.1002/ana.21154
|View full text |Cite
|
Sign up to set email alerts
|

TDP‐43 immunoreactivity in hippocampal sclerosis and Alzheimer's disease

Abstract: Goal-This study aimed to determine the frequency of frontotemporal lobar degeneration with ubiquitinated inclusions (FTLD-U) in the setting of hippocampal sclerosis (HpScl) and Alzheimer's disease (AD) using immunohistochemistry for TAR DNA binding protein 43 (TDP-43), a putative marker for FTLD-U.Methods-Initially, 21 cases of HpScl associated with a variety of other pathologic processes and 74 cases of AD were screened for FTLD-U with TDP-43 immunohistochemistry. A confirmation study was performed on 93 addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

54
713
11
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 783 publications
(806 citation statements)
references
References 36 publications
54
713
11
5
Order By: Relevance
“…TDP-43 has been discovered in both sporadic and familial AD [46][47][48] , and our seeding results showed that TDP-43 oligomers can interact and influence Ab fibrillization. The increased Ab assembly in the presence of TDP-43 could result from a seeding effect that generates new Ab assemblies such as Ab*56 and larger aggregates or formation of cross-linked TDP-43 and Ab complexes.…”
Section: Discussionmentioning
confidence: 53%
“…TDP-43 has been discovered in both sporadic and familial AD [46][47][48] , and our seeding results showed that TDP-43 oligomers can interact and influence Ab fibrillization. The increased Ab assembly in the presence of TDP-43 could result from a seeding effect that generates new Ab assemblies such as Ab*56 and larger aggregates or formation of cross-linked TDP-43 and Ab complexes.…”
Section: Discussionmentioning
confidence: 53%
“…TDP-43 is the major component of neuronal inclusions, the histopathological hallmark of both ALS and the most frequent subtypes of frontotemporal dementia (FTD), considered the second most common early-onset dementia, characterized by neuronal loss in the frontal and temporal cortex. 6,7 In fact, cytoplasmic TDP-43 accumulation also represents a secondary pathological feature of other major neurodegenerative diseases, including Alzheimer's disease, 8 Parkinson's disease, 9 and Huntington's disease. 10 Despite increasing evidence suggesting a critical role of TDP-43 in disease progression in these various major neurodegenerative diseases, the pathogenic mechanisms underlying TDP-43 are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a 400% increase of GRN expression has been observed in the spinal cord of patients with ALS [Malaspina et al, 2001] and Creutzfeldt-Jakob disease (CJD) [Baker and Manuelidis, 2003], most likely as a result of the activation of microglia. In AD and Lewy-body related diseases, TDP-43 immunoreactivity was also observed [Amador-Ortiz et al, 2007;Nakashima-Yasuda et al, 2007;Higashi et al, 2007]. In addition, FTLD and AD are sometimes difficult to differentiate at diagnosis and their key symptoms can be accompanied by parkinsonism, also occuring in FTLD patients carrying a GRN null mutation Mackenzie, 2007].…”
Section: Introductionmentioning
confidence: 99%